1981
DOI: 10.1063/1.863452
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent boundary layer at low Reynolds number

Abstract: Symmetry analysis and self-similar forms of fluid flow and heat-mass transfer in turbulent boundary layer flow of a nanofluid Phys. Fluids 24, 092003 (2012) Detuned resonances of Tollmien-Schlichting waves in an airfoil boundary layer: Experiment, theory, and direct numerical simulation Phys. Fluids 24, 094103 (2012) Asymptotic expansion of the solution of the steady Stokes equation with variable viscosity in a two-dimensional tube structure J. Math. Phys. 53, 103702 (2012) Large-eddy simulation of turbulent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
88
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(115 citation statements)
references
References 9 publications
25
88
1
1
Order By: Relevance
“…in experiment 1) is in good agreement with other experiment at low Reynolds number [6]. Due to the variation of density, the corresponding friction velocity ) ) / ( (…”
Section: 33-skin Frictionsupporting
confidence: 87%
See 1 more Smart Citation
“…in experiment 1) is in good agreement with other experiment at low Reynolds number [6]. Due to the variation of density, the corresponding friction velocity ) ) / ( (…”
Section: 33-skin Frictionsupporting
confidence: 87%
“…On the other hand, because of the weak size of the wire and its moderate overheating, this one doesn't affect the response of the film. In homogeneous boundary layer which develops on the plate, the profiles of the longitudinal mean velocity and of its turbulent intensity measured with such a probe are in good agreement with other data [6]. The density at the wall W is measured directly by an aspirating probe which is insensitive to velocity fluctuations and the skin friction is given by a flush-mounted hot-film located in the same section (Fig.…”
Section: 3-instrumentationsupporting
confidence: 80%
“…Any deviation between "optical" C f , computed from equation (15), and true C f simply indicates that the scaling assumptions are not valid at this Reynolds number. Figure 9 shows estimated values of C f , with error bars, from the OPD rms measurements; Figure 9 demonstrates that values of skinfriction "computed" from heated-wall wavefront measurements are consistent with experimental measurements of C f from Hama [19], Purtell, et al [20], Schultz-Grunow [21], and Österlund [22] in the low-Reynolds number range. From here we concluded that the prediction for OPD rms , equation (7), should be valid for Re θ > 4,000.…”
Section: B Calculation Of Opd Rms (δT = 0) From Heated Wall Datasupporting
confidence: 67%
“…The initial turbulence spectrum was Iu(k)l -k2 exp -k2/4, with the u(k) having random phase; the total initial turbulent energy was 0.0025. There was an initial transient period during which the value of A in (7) was increased to A = 1.5 (from A = O.l), and the viscosity in (6) was decreased to Y = 0.0005 (from v = 0.001). After a quasi-steady state appeared to become established, the values of all the Fourier coefficients u(k) were saved for all integer values o f t from t = 150 to t = 650, inclusive, for a total of 501 time slices upon which to perform statistical evaluation.…”
Section: Resultsmentioning
confidence: 99%